The Social and Literary Type of Quranic Interpretation in Egypt and Indonesia (A Comparative Study between Abduh and Quraish) | لون الأدبي الإجتماعي في التفسير في مصر وفي إندونيسيا (دراسة مقارنة بين عبده وقريش ) - Faizah Ali Syibromalisi (Al-Zahra : Journal for Islamic and Arabic Studies, 2018)
The research talks about the idea of renewing exegesis in Egypt and in Indonesia towards its social literary colour. It became inevitable to conduct the discussion of the renewal of exegesis - whether in Egypt or Indonesia - in the social literary direction through the important issues focused by the interpreters recently. Their efforts of renewing revealed, and where Egypt was the reference to the first source and this concept. The article discusses the concept of renewing from Mohammed Abduh, the owner of Al Manar School in Egypt, and Muhammad Quraish Shihab, the author of tafsir al-Mishbah in Indonesia. The writer attempts to analyze the characteristic of social and literary on both methods of exegesis. Also, to know the influence of Mohammed Abduh in Quraish’s book through the originality and methodology applied in it